2011
DOI: 10.1162/jocn.2010.21537
|View full text |Cite
|
Sign up to set email alerts
|

Control of Reflexive Saccades following Hemispherectomy

Abstract: Abstract■ Individuals who have undergone hemispherectomy for treatment of intractable epilepsy offer a rare and valuable opportunity to examine the ability of a single cortical hemisphere to control oculomotor performance. We used peripheral auditory events to trigger saccades, thereby circumventing dense postsurgical hemianopia. In an antisaccade task, patients generated numerous unintended short-latency saccades toward contralesional auditory events, indicating pronounced limitations in the ability of a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
(78 reference statements)
2
3
1
Order By: Relevance
“…These later studies clearly demonstrated that the common area of damage between patients affected the precentral sulcus, between the superior and inferior frontal sulci, and the adjacent parts of the precentral and middle frontal gyri ( Figure 2). Note that, as in the monkey, unilateral FEF lesions present mainly contralateral saccade impairment (but see Reuter-Lorenz et al, 2011). In a more general point of view, human studies for the most part are consistent with the findings reported in monkeys, namely lesions of the peri-precentral cortex in humans and adjacent to the arcuate sulcus in monkeys lead to voluntary saccadic eye movements impairments.…”
Section: A Lesion Definitionsupporting
confidence: 81%
“…These later studies clearly demonstrated that the common area of damage between patients affected the precentral sulcus, between the superior and inferior frontal sulci, and the adjacent parts of the precentral and middle frontal gyri ( Figure 2). Note that, as in the monkey, unilateral FEF lesions present mainly contralateral saccade impairment (but see Reuter-Lorenz et al, 2011). In a more general point of view, human studies for the most part are consistent with the findings reported in monkeys, namely lesions of the peri-precentral cortex in humans and adjacent to the arcuate sulcus in monkeys lead to voluntary saccadic eye movements impairments.…”
Section: A Lesion Definitionsupporting
confidence: 81%
“…No auditory gap effect was found for SRTs or error rates. In contrast to this, previous findings in adults have described a smaller, but still significant gap effect for acoustically cued saccades [ 17 , 23 - 25 ]. It might be the case for children that although mean SRTs indicate a gap-effect, it is obscured by a relatively high SRT variablity (208 ms gap, 209 ms overlap condition).…”
Section: Discussioncontrasting
confidence: 99%
“…This reaction is already present in babies [ 16 ]. Although saccades towards acoustic targets are scientifically less well investigated than saccades towards visual targets, a recent study delineated an "acoustic-evoked ocular grasp reflex" in adults [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations